Efficacy of oral tofacitinib in moderate to severe alopecia areata, totalis and universalis at the tertiary care hospital, Karachi - Qadir, Misbah Zari; Ghafoor, Rabia; Salahuddin, Muhammad Khurram; Sanawar, Parisa; Jabeen, Nazia; Asadullah, Khadija (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the effectiveness and safety of oral tofacitinib in treating patients with different forms of alopecia. Method: The prospective, interventional, open-label study was conducted at the Department of Dermatology, Jinnah Postgraduate Medical Centre, Karachi, from November 2023 to April 2024, and comprised cases of alopecia areata, totalis and universalis. Tofacitinib 5mg twice daily was prescribed, and the Severity of Alopecia Tool score was evaluated at baseline, and then again at 6 weeks, 12 weeks and 24 weeks. Data was analysed using SPSS 23. Results: Of the 30 subjects with mean age 26.53±4.77 years (range: 19-36 years), 15(50%) were males and 15(50%) were females. The mean Severity of Alopecia Tool score at baseline was 88.41±11.59, which decreased to 74.75±13.88 at 6 weeks, 58.51±20.96 at 12 weeks, and 45.88±23.63 at 24 weeks. Overall, 24(80%) patients showed improvement at 24 weeks in terms of hair regrowth. No adverse events were noted in any patient. Conclusion: The efficacy and safety of tofacitinib in the treatment of alopecia areata showed promising results, and it could be a viable treatment option for alopecia. Key Words: Tofacitinib, Alopecia areata, Alopecia totalis, Alopecia universalis, Janus kinase inhibitor, Therapeutic efficacy.